Bilayer Networks within a Hydrogel Shell: A Robust Chassis for Artificial Cells and a Platform for Membrane Studies. Issue 46 (11th October 2016) - Baxani, Divesh K.; Morgan, Alex J. L.; Jamieson, William D.; Allender, Christopher J.; Barrow, David A.; Castell, Oliver K.
Abstract: The ability to make artificial lipid bilayers compatible with a wide range of environments, and with sufficient structural rigidity for manual handling, would open up a wealth of opportunities for their more routine use in real‐world applications. Although droplet interface bilayers (DIBs) have been demonstrated in a host of laboratory applications, from chemical logic to biosynthesis reaction vessels, their wider use is hampered by a lack of mechanical stability and the largely manual methods employed in their production. Multiphase microfluidics has enabled us to construct hierarchical triple emulsions with a semipermeable shell, in order to form robust, bilayer‐bound, droplet networks capable of communication with their external surroundings. These constructs are stable in air, water, and oil environments and overcome a critical obstacle of achieving structural rigidity without compromising environmental interaction. This paves the way for practical application of artificial membranes or droplet networks in diverse areas such as medical applications, drug testing, biophysical studies and their use as synthetic cells. Abstract : Encapsulated droplet networks : Droplet networks separated by lipid membranes are encapsulated within a semi‐permeable shell. These cell‐like materials can spatially segregate defined compartments and communicate with the outside world using reconstituted membrane proteins. Such microfluidically prepared membrane constructs are stable in a range of environments.